2009 2nd International Conference on Adaptive Science &Amp; Technology (ICAST) 2009
DOI: 10.1109/icastech.2009.5409740
|View full text |Cite
|
Sign up to set email alerts
|

Route discovery in wireless mobile ad hoc networks with adjusted probabilistic flooding

Abstract: Message flooding has been extensively used in wireless mobile ad hoc networks for activities such as route and resource discovery. This can potentially lead to high channel contention, causing redundant retransmissions and thus excessive packet collisions in the network. Such a phenomenon has been shown to greatly increase the network communication overhead and endto-end delay. In this paper, we propose a probabilistic method of flooding that adjusts the forwarding probability at a node using its local topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…But pull algorithms are difficult to carry out [15]. Similarly, the authors in [2] distinguish all sites by four levels. The probability in each level is reversely proportional to the number of levels predefined in ad hoc network.…”
Section: Related Workmentioning
confidence: 97%
“…But pull algorithms are difficult to carry out [15]. Similarly, the authors in [2] distinguish all sites by four levels. The probability in each level is reversely proportional to the number of levels predefined in ad hoc network.…”
Section: Related Workmentioning
confidence: 97%
“…As explained in Section V, our model produces the same result for GossipFF and GossipPISB, depicted as ModelFF. For a given p f orw , we can theoretically have both the reliability by our model and the message complexity M shown in Equation (2).…”
Section: Table I Topology Parametersmentioning
confidence: 99%
“…The authors distinguish all sites by four levels in [2]. Then, the probability in each level is reversely adapted to the number of levels predefined in sensor network.…”
Section: Table I Topology Parametersmentioning
confidence: 99%
“…The proposed method can significantly reduce the number of RREQ packets transmitted during route discovery operation. Similarly, in [5] the authors proposed a probabilistic method of flooding that adjusts the forwarding probability at a node using its local topological characteristics. Unlike the first two, Li Jian et al [6] proposed a Positional Attribute based Next-hop Determination Approach and identified the "next-hop racing" phenomena due to the random rebroadcast delay approach during the route discovery process.…”
Section: Related Workmentioning
confidence: 99%